The Commodification of Healthcare in the United States and the Spirituality of Social Transformation for Catholic Healthcare Professionals - Ballano, Vivencio O. (Transformation, 2025)
This article explores how the Catholic Church's teaching on the spirituality of social transformation can be used by Catholic health professionals against the growing commodification of health care in the United States. Using the qualitative research method that uses secondary literature, it argues that living out the spirituality of social transformation against commodification in the healthcare industry implies imitating Christ's healing ministry and doing social action by physicians and healthcare workers to protect human dignity in medical research, to see health care work as a vocation, to give preferential treatment for poor patients, and to exercise prudence and Christian discernment in dealing with corporate medicine.